2016
DOI: 10.1097/moo.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and treatment of isolated sphenoid sinus diseases

Abstract: Isolated sphenoid sinus diseases are uncommon, with nonspecific clinical presentation. Early diagnosis requires a high index of clinical suspicion, proper endoscopic nasal examination, and appropriate radiological imaging. Surgical intervention is the primary treatment modality for most of the isolated sphenoid sinus diseases. Endoscopic endonasal approach to sphenoid sinus is the technique of choice. The location of sphenoid sinus disease, the extent of the surgery, and anatomic configuration of the sphenoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…6 Several endoscopic endonasal approaches have been described: the transseptal sphenoidotomy, the transethmoidal sphenoid approach and the transpterygoid approach. [11][12][13] Transseptal sphenoidotomy did not provide an adequate visualization of the SSLR. The transethmoidal sphenoid approach permitted removal of the pterygoid process medial to the Vidian canal but was not wide enough to repair the CSF rhinorrhea in the SSLR.…”
Section: Discussionmentioning
confidence: 92%
“…6 Several endoscopic endonasal approaches have been described: the transseptal sphenoidotomy, the transethmoidal sphenoid approach and the transpterygoid approach. [11][12][13] Transseptal sphenoidotomy did not provide an adequate visualization of the SSLR. The transethmoidal sphenoid approach permitted removal of the pterygoid process medial to the Vidian canal but was not wide enough to repair the CSF rhinorrhea in the SSLR.…”
Section: Discussionmentioning
confidence: 92%
“…1,5 High index of suspicion among otolaryngologists and neurologists dealing with such patients is essential to make an early diagnosis. 10,14 Computed tomography is the investigation of choice in patients who are suspected of having ISSD. 10,15 It has been reported that nearly 22% of ISSD are detected incidentally on computed tomography.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, previous studies have implicated surgical intervention in 80-100% of ISSD. 1,3,6,[8][9][10][11][12]14 On the other hand, a selected few uncomplicated case of acute or chronic sphenoiditis can be successfully managed by conservative management with antibiotics and antihistamines. 4,10,13,18 Like in our surgical cohort, the procedure of choice for surgery in all these published reports of ISSD is endoscopic sphenoidotomy and disease clearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire comprised four scales adapted from previous research. We used three seven-point semantic differential scale items adapted from Lafferty and Goldsmith ( 2005 ) to measure attitude. We assessed CSR associations with a four-item Likert scale adapted from Dean ( 2002 ).…”
Section: Methodsmentioning
confidence: 99%